Oversize packaging and sustainability : the case of ready-to-eat cereals in Portugal - Ribeiro, Teresa Raquel dos Santos (2017)
Packaging remains an under-researched topic, namely packaging size optimization. Packaging is central to the economic organization of food and to the sustainable companies’ logistics function. This research examines packaging oversizing in the breakfast cereal segment of the Portuguese market, in a study that analyzes a sample of 109 cereal packages. A substantial share of the ready-to-eat breakfast cereal brands analysed presented an excessive amount of package, which means they are oversized. The findings show that a reduction of 20% of package height for all the categories studied is feasible. The consumers’ awareness regarding carton box format oversizing on cereal packages and the consumers’ preferences regarding breakfast cereals is also evaluated. Finally, a reflection on the consequences of the superfluous package and the benefits of reducing the amount of ready-to-eat breakfast packages is presented in the conclusions.